BAHASA INGGRIS BAHASA INGGRIS - Ma'rufi, Lady Maysuri Ma'rufi; Rohana, Rohana; Makkasau , Andi (PT Ininnawa Paramacitra Edukasi, 2025)
This study was motivated by the low learning outcomes of fourth-grade students at SDN 12 Babana, Bulukumba Regency, in the topic of motion energy. The main cause identified was the use of conventional lecture methods, which made students passive and less motivated to learn. Therefore, this research aimed to improve students’ learning outcomes on motion energy through the application of the Student Teams Achievement Divisions (STAD) cooperative learning model assisted by audio-visual media. This research employed a quantitative approach with an experimental method using a Quasi-Experimental Design. The population consisted of all fourth-grade students at SDN 12 Babana, with samples selected through probability sampling. Data were collected through learning outcome tests and classroom observations. The data analysis employed descriptive and inferential statistics, including normality tests, homogeneity tests, and hypothesis testing using the independent sample T-test. The results showed that the STAD cooperative learning model assisted by audio-visual media was effective in enhancing students’ learning outcomes. This effectiveness was evident in the increased student engagement during the learning process and the significant improvement in test scores after the treatment compared to before. In conclusion, the implementation of the STAD cooperative learning model assisted by audio-visual media had a positive and significant effect on improving motion energy learning outcomes among fourth-grade students at SDN 12 Babana, Bulukumba Regency.